2014
DOI: 10.1248/bpb.b14-00099
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone Derivatives Inhibit Human Platelet Aggregation and Inhibit Growth in Human Bladder Cancer Cells

Abstract: In an effort to develop potent cyclooxygenase-1 (COX-1) inhibitors used as anticancer agent, a series of 2′,5′-dimethoxychalcones was screened to evaluate their antiplatelet effect on human washed platelets suspension. Compound 2 exhibited potent inhibition of human washed platelet aggregation induced by collagen, significantly inhibited collagen-and arachidonic acid-induced thromboxane B 2 release, and revealed inhibitory effect on COX-1 activity. Molecular docking studies showed that 1, 2, and 4 were bound i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Evidence from epidemiologic studies supports a potential role for some flavonoids in the reduction of cardiovascular risk. For instance, flavonoids are able to prevent against endothelial dysfunction through averting oxidation of low-density lipoproteins (LDL) [ 6 ], platelet aggregation and adhesion [ 7 ], and smooth muscle cell migration and proliferation [ 8 ]. Moreover, according to recent data aiming to evaluate association between dietary flavonoid intake and cardiovascular risk through analyses of prospective cohort studies, it has been reported that intakes of epigallocathechin gallate (EGCG) (relative risk: 0.87; 95% confidence interval: 0.80, 0.95) were inversely associated with the risk of cardiovascular diseases [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from epidemiologic studies supports a potential role for some flavonoids in the reduction of cardiovascular risk. For instance, flavonoids are able to prevent against endothelial dysfunction through averting oxidation of low-density lipoproteins (LDL) [ 6 ], platelet aggregation and adhesion [ 7 ], and smooth muscle cell migration and proliferation [ 8 ]. Moreover, according to recent data aiming to evaluate association between dietary flavonoid intake and cardiovascular risk through analyses of prospective cohort studies, it has been reported that intakes of epigallocathechin gallate (EGCG) (relative risk: 0.87; 95% confidence interval: 0.80, 0.95) were inversely associated with the risk of cardiovascular diseases [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic analogs and derivatives of the molecule are increasingly getting into focus due to their promising therapeutic potential. Chalcone derivatives are reported to exhibit anti-cancer effects in several cancer cell lines, such as human acute leukemia cells [ 8 ], colon cancer cells [ 9 , 10 ], human bladder cancer cells [ 11 ], and lung cancer cells [ 12 ]. In addition, as anticancer therapeutic agents, chalcones have advantages such as poor interaction with DNA and low risk of mutagenesity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…By inhibiting the angiotensin-converting enzyme (ACE) and inducing high vasodilation, the anti-hypertensive effect of amino-chalcones has been demonstrated in vitro and in vivo on rats, rabbits, and dogs [25,26]. Several molecular targets such as cyclooxygenase [27] and potassium channels [28], metabolism pathways such as triacylglycerol synthesis pathway [29][30][31] and pro-angiogenic properties [32] have also been identified to explain the potential role of chalcones in the prevention and/or treatment of cardiovascular diseases. However, all these effects have been mainly highlighted with functionalized chalcones bearing amino, prenyl or sulfonyloxy groups and little data are available for polyoxygenated chalcones [25].…”
Section: Discussionmentioning
confidence: 99%